Ankle brachial index and cognitive function among Hispanics/Latinos: Results from the Hispanic Community Health Study/Study of Latinos. (April 2018) - Tarraf, Wassim; Criqui, Michael H.; Allison, Matthew A.; Wright, Clinton B.; Fornage, Myriam; Daviglus, Martha; Kaplan, Robert C.; Davis, Sonia; Conceicao, Alan S.; González, Hector M.
Abstract: Background and aims: The Ankle-Brachial index (ABI) is a well-accepted measure of peripheral artery disease (arterial stenosis and stiffness) and has been shown to be associated with cognitive function and disorders; however, these associations have not been examined in Hispanics/Latinos. Therefore, we sought to examine relationships between ABI and cognitive function among diverse middle-age and older Hispanics/Latinos. Methods: We used cross-sectional data on n = 7991 participants aged 45–74 years, without stroke or coronary heart disease, from the Hispanic Community Health Study/Study of Latinos. Our primary outcome, global cognition (GC), was a continuous composite score of four cognitive domains (verbal learning and memory, verbal fluency, executive function, and mental status). Secondary outcomes were the individual tests representing these domains. The ABI was analyzed continuously and categorically with standard clinical cut-points. We tested associations using generalized survey regression models incrementally adjusting for confounding factors. Age, sex, hypertension, diabetes, and dyslipidemia moderations were examined through interactions with the primary exposure. Results: In age, sex, and education adjusted models, continuous ABI had an inverse u-shape association with worse GC. We found similar associations with measures of verbal learning and memory, verbal fluency, executive function, but not with low mental status. The associations were attenuated, but not completely explained, by accounting for the confounders and not modified by age, sex, education, and vascular disease risks. Conclusions: In addition to being a robust indicator of arterial compromise, our study suggests that abnormal ABI readings may also be useful for early signaling of subtle cognitive deficits. Highlights: Both low and high ABI are associated with worse cognition in diverse Hispanics/Latinos (H/Ls). The associations are independent of, and not modified by, age, sex, education, and other vascular risks. ABI may offer a feasible avenue for early signaling of risk for cognitive dysfunction in middle-age diverse H/Ls.